The first ten years of activity of S.N.P.J. - Blagotinšek Turk, Metoda (Two Homelands, 2001)
The contribution describes the foundation and the first ten years of the activity of the Slovenska narodno podporna jednota (Slovene National Benefit Society). The author deals with the reasons for founding the SNPJ, and describes how this fraternal benefit society differentiated from the other Slovene fraternal organisations. The basic function of the SNPJ is presented, that is, insurance and all other functions the SNPJ practised. The SNPJ had the role of insurance companies, as the USA did not know of social insurance at that time. Beside that basic function the SNPJ also performed the role of cultural and political unifier of Slovene emigrants in the USA.